PENILE FRACTURE ASSOCIATED WITH URETHRAL INJURY – CASE REPORT - Prijović, Nebojša; Stanković, Branko; Radovanović, Milan; Šantrić, Veljko; Babić, Uroš (Srpski medicinski časopis Lekarske komore, 2026)
Introduction: Penile fracture is a rare urologic emergency that may occur when the erect penis is injured, most often during sexual intercourse. In 10%-21% of cases, it is associated with urethral injury. The diagnosis is most often made by clinical examination, but additional diagnostic methods are useful in evaluating the site of rupture of the corpora cavernosa and detecting urethral injury. This medical emergency requires urgent surgical management as delays are associated with worse outcomes. Case report: A 43-year-old man reported to the Emergency Center of the University Clinical Center of Serbia due to an injury to the erect penis during sexual intercourse. The anamnestic data were that he had felt pain and heard a “popping” sound, upon which sudden detumescence of the penis occurred and penile hematoma appeared, as well as blood during urination. Suspicion of a penile fracture was established on clinical examination. An ultrasound examination showed a rupture of the tunica albuginea of the right cavernous body, and retrograde urethrocystography revealed a rupture of the penile urethra. The patient underwent surgery that same evening. The surgical approach was a median penoscrotal incision, followed by suturing of the right cavernous body and penile urethra through a gently placed urinary catheter. Postoperative recovery was uneventful. During follow-up examinations, the patient reported normal erections, regular urination and satisfaction with the appearance of his penis. Conclusion: Penile fracture is a rare urologic emergency, which is relatively rarely associated with urethral injury. The presentation of our case indicates the importance of initial ultrasound and radiographic diagnostics. In the case where the site of injury is present preoperatively, a ventral penoscrotal incision may be a suitable surgical approach. Timely recognition and surgical treatment of penile fracture associated with urethral injury gives excellent functional results.
Keywords: penile fracture; urethral injury; urologic emergency; urgent surgical management